Case report: A third variant in the 5′ UTR of TWIST1 creates a novel upstream translation initiation site in a child with Saethre-Chotzen syndrome - Diaz-Gonzalez, Francisca; Sacedo-Gutiérrez, Javier M.; Twigg, Stephen R. F.; Calpena, Eduardo; Carceller-Benito, Fernando E.; Parrón-Pajares, Manuel; Santos-Simarro, Fernando; Heath, Karen E. (Frontiers in Genetics, 2023)
Introduction: Saethre-Chotzen syndrome, a craniosynostosis syndrome characterized by the premature closure of the coronal sutures, dysmorphic facial features and limb anomalies, is caused by haploinsufficiency of TWIST1. Although the majority of variants localize in the coding region of the gene, two variants in the 5´ UTR have been recently reported to generate novel upstream initiation codons. Methods: Skeletal dysplasia Next generation sequencing (NGS) panel was used for genetic analysis in a patient with bicoronal synostosis, facial dysmorphisms and limb anomalies. The variant pathogenicity was assessed by a luciferase reporter promoter assay. Results: Here, we describe the identification of a third ATG-creating de novo variant, c.-18C>T, in the 5´ UTR of TWIST1 in the patient with a clinical diagnosis of Saethre-Chotzen syndrome. It was predicted to create an out-of-frame new upstream translation initiation codon resulting in a 40 amino acid larger functionally inactive protein. We performed luciferase reporter promoter assays to demonstrate that the variant does indeed reduce translation from the main open reading frame. Conclusion: This is the third variant identified in this region and confirms the introduction of upstream ATGs in the 5´ UTR of TWIST1 as a pathogenic mechanism in Saethre-Chotzen syndrome. This case report shows the necessity for performing functional characterization of variants of unknown significance within national health services.